The Role of Internet and its Applications in Spreading Rumors - عيساني رحيمة الطيب (ALBAHITH ALALAMI, 2015)
The study tries to answer several questions posed by the subject, one of the important: How the Internet promotes rumor? And what are the most Internet applications that promote rumor? And the practical ways to reduce these negative? Using the process of in vestige and reading theoretical heritage available in this field, and inferred the numbers and statistics marked the uses of the Internet and its applications over recent years, and the characteristics of each these tools in the field of collection, processing, and dissemination of information